An analysis of the pacing strategies adopted by elite cross-country skiers - Losnegard, T.; Kjeldsen, K.; Skattebo, Ø. (The Journal of Strength and Conditioning Research, 2016)
Understanding the pacing strategies used by the most successful skiers may provide insight into the most desirable pacing approach in cross-country (XC) skiing. This study examined the pacing strategies adopted by male and female XC skiers of different performance standards during 10 and 15 km races in World Cup, World Championships, and Olympic events. Analyses were performed on races involving 5 km laps in the men's 15 km (number of races = 22) and the women's 10 km (n = 14) individual start races (classic and freestyle) from season 2002/2003 to season 2013/2014. Final rank and lap times for the 40 top finishers in each race were analyzed. Both sexes demonstrated a positive pacing pattern shown by a decline in velocity from the first to the last lap (men: 6.76 ± 0.43 m/s vs. 6.47 ± 0.46 m/s; p < 0.001; women: 6.0 ± 0.47 m/s vs. 5.87 ± 0.53 m/s; p < 0.001). For the men, slower skiers (final ranking 21st-30th and 31st-40th) were characterized by a quick start relative to their average velocity, with a greater decrease during the race compared with the fastest skiers (1st-10th) (p = 0.007 and p < 0.001, respectively). For the women, no group differences in pacing strategy were found. In conclusion, this study shows that the pacing strategy indicates the standard of elite male XC skiers. Examining the pacing strategies of the best male performers suggests that lower-performing male skiers should consider a more even pacing strategy to improve their performance.